Asparaginyl-tRNA Synthetase, a Novel Component of Hippo Signaling, Binds to Salvador and Enhances Yorkie-Mediated Tumorigenesis - Yeom, Eunbyul; Kwon, Dae-Woo; Lee, Jaemin; Kim, Seok-Ho; Lee, Ji-Hyeon; Min, Kyung-Jin; Lee, Kyu-Sun; Yu, Kweon (Frontiers in Cell and Developmental Biology, 2020)
Aminoacyl-tRNA synthetases (ARSs), which are essential for protein translation, were recently shown to have nontranslational functions in various pathological conditions including cancer. However, the molecular mechanism underlying the role of ARSs in cancer remains unknown. Here, we demonstrate that asparaginyl-tRNA synthetase (NRS) regulates Yorkie-mediated tumorigenesis by binding to the Hippo pathway component Salvador. NRS-RNAi and the NRS inhibitor tirandamycin B suppressed Yorkie-mediated tumor phenotypes in Drosophila. Genetic analysis showed that NRS interacted with Salvador, and NRS activated Hippo target genes by regulating Yorkie phosphorylation. Biochemical analyses showed that NRS blocked Salvador-Hippo binding by interacting directly with Salvador, and tirandamycin B treatment inhibited NRS-Salvador binding. YAP target genes were upregulated in a mammalian cancer cell line with high expression of NRS, whereas tirandamycin B treatment suppressed cancer cell proliferation. These results indicate that NRS regulates tumor growth by interacting with Salvador in the Hippo signaling pathway.